If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2x + 2) + -2x + 2 = -26 Reorder the terms: -4(2 + 2x) + -2x + 2 = -26 (2 * -4 + 2x * -4) + -2x + 2 = -26 (-8 + -8x) + -2x + 2 = -26 Reorder the terms: -8 + 2 + -8x + -2x = -26 Combine like terms: -8 + 2 = -6 -6 + -8x + -2x = -26 Combine like terms: -8x + -2x = -10x -6 + -10x = -26 Solving -6 + -10x = -26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -10x = -26 + 6 Combine like terms: -6 + 6 = 0 0 + -10x = -26 + 6 -10x = -26 + 6 Combine like terms: -26 + 6 = -20 -10x = -20 Divide each side by '-10'. x = 2 Simplifying x = 2
| 10d-6d+3d=7 | | 3x=5x-10x | | 3a-a-a+a=20 | | 2.5(b+87)=3212 | | 15=-15+8u | | -10j-13j+14j=18 | | -6x+5.8=23.8 | | 7/4y-5/6y | | 5x^2+10y^2=4 | | 10v-v-7v+v+3v=18 | | 3x-6y=-46.5 | | secx+2tanx=0 | | 1.2=1+k^6 | | D=R(100-x)/100 | | 1/3w=31/4 | | -37-(-48)= | | 4x+6=-10 | | 23x^2-29=0 | | -7(0.1x+0.2)-1.1=-0.4 | | 4*-4+6=-10 | | 69=5v-11 | | 0/1= | | (3a-7)(4a-b-2)-(3a+4b)(3a+4b)= | | -6/7= | | y/2-12=11 | | b-4/5=9/10 | | 0.50x+0.05(10-x)=0.10(-49) | | 25=3+2x+5x+4 | | 5a+13=6a-5 | | -3-y=-15 | | 7n^2+37n+20=4n | | 4X(w+3)=w-15 |